Examination and clinical correlation of olfactory system disorders by an objective method Sniffin’ Sticks odor test in Parkinson’s disease - Turkmen, Nur; Sücüllü Karadağ, Yeşim; Öztekin, Zeynep Neşe (The European Research Journal, 2021)
Objectives: This study is aimed to investigate the frequency of olfactory dysfunction in Parkinson’s Disease (PD) and its relationship with motor/non-motor symptoms and treatment in comparison to isolated olfactory dysfunction patients and healthy controls. Methods: This study includes 40 PD patients, 37 anosmia patients and 42 healthy controls. PD patients are evaluated with PD evaluation form including; sociodemographic features, disease history, Unified Parkinson’s Disease Rating Scale (UPDRS) score, and Hoehn and Yahr (H-Y) score. All patients were evaluated with cranial CT and MRI. Olfactory function was evaluated with Sniffin’ Sticks Test (SST). A p value < 0.05 was considered to be statistically significant. Results::The mean age and median disease duration of PD patients were 62.2 ± 11.9 and 4.5 years, respectively. Fifteen of them had comorbid diseases. Median UPDRS score was 19.5 (4-60) and 67.5% of subjects were H-Y Stage-1. Most frequent non-motor symptom was constipation (67.5%). Olfactory dysfunction was found in 75% of PD patients by SST. No difference was observed between PD patients with or without olfactory dysfunction regarding non-motor symptoms and dementia (p > 0.05). Patients with isolated olfactory dysfunction were significntly younger than both patients with PD and the healthy controls (p <0.001). Non-motor symptoms were not significantly different between isolated olfactory dysfunction group and healthy subjects (p > 0.05). ﻿ Conclusions: Most of the patients with PD had olfactory dysfunction, which was found not to be correlated with disease duration and stage based on the results of an objective test, namely Sniffin-Sticks odor test.This result might support the role of non-dopaminergic pathways in the etiopathogenesis of olfactory dysfunctions in PD. In clinical practice, data from further studies is required to comment on an ideal screening or diagnostic test in the olfactory system evaluation of early stage PD patients that would be repeatable and objective.